2019
DOI: 10.1111/bdi.12851
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and polygenic risk in bipolar disorders

Abstract: Background Childhood maltreatment is a well‐known risk factor for developing a more severe and complex form of bipolar disorders (BD). However, knowledge is scarce about the interactions between childhood maltreatment and underlying genetic vulnerability on the clinical expression of BD. Method We assigned a BD‐polygenic risk score (BD‐PRS), calculated from the Psychiatric Genomics Consortium, to each individual in a sample of 402 cases with BD. The lifetime clinical expression of BD was characterized using st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Recent studies have suggested that a high BD-PRS may be associated with the presence of psychotic features during mood episodes 17,18 , while BD-PRS has been suggested to not be associated with an earlier AAO 19 . An additional recent study reported the interaction between childhood maltreatment and PRS in patients with BD and found that BD-PRS and childhood maltreatment interacted to increase the risk of rapid cycling 11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have suggested that a high BD-PRS may be associated with the presence of psychotic features during mood episodes 17,18 , while BD-PRS has been suggested to not be associated with an earlier AAO 19 . An additional recent study reported the interaction between childhood maltreatment and PRS in patients with BD and found that BD-PRS and childhood maltreatment interacted to increase the risk of rapid cycling 11 .…”
Section: Discussionmentioning
confidence: 99%
“…From this cohort, we obtained 1 615 subjects with BD I, who were of European ancestry to heighten homogeneity. Participants provided written informed consent according to institutional review board protocols and were evaluated using the Diagnostic Interview for Genetic Studies (DIGS) 11,13 . DIGS is a specific clinical interview for evaluating mood and psychotic disorders through a semistructured design corresponding to a wide spectrum of DSM-IV criteria.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding environmental risk contributing to T2D in BD, several studies report an unhealthy life style in patients including physical inactivity especially in depressive phases (26,27), higher alcohol and illegal substance consumption, nicotine dependence and greater intake of unhealthy food (28)(29)(30)(31), and increased rates of psychological trauma/maltreatment in childhood (32,33). Additionally, several endocrine and metabolic pathways could be playing a role in conveying a greater risk of T2D in BD, such as dysregulation of different neuropeptides (for example leptin, ghrelin, and adiponectin) and disturbances in the hypothalamus-pituitary-adrenal gland axis (34,35).…”
Section: Introductionmentioning
confidence: 99%